Does Perceived Organizational Support Mediate The Relationship Between Human Resource Management Practices And Organizational Commitment? - Mohd. Nasurdin, Aizzat; Hemdi, Mohamad Abdullah; Lye , Phei Guat (Asian Academy of Management (AAM), 2008)
This study examines a model involving Human Resource Management (HRM) practices, perceived organizational support, and organizational commitment. It was hypothesized that HRM practices (performance appraisal, training and career development) will be positively related to organizational commitment, and that perceived organizational support would serve as a mediator in the relationship between HRM practices and commitment. The statistical results on data gathered from a sample of 214 employees within the Malaysian manufacturing sector demonstrated that career development and performance appraisal have direct, positive and significant relationships with organizational commitment. In addition, perceived organizational support was found to partially mediate the relationships between two of the three HRM practices (career development and performance appraisal) and commitment. Theoretical and managerial implications are suggested.